MOTIVASI DAN DISIPLIN KERJA PENGARUHNYA TERHADAP KINERJA PEGAWAI PADA BIDANG PENDAFTARAN DAN INFORMASI PENDUDUK DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BEKASI JAWA BARAT - Firstly Dito Pranata, Asri Warnanti (Prosiding Seminar Nasional, 2014)
The purpose of this study is to know the influence of work motivation and discipline at employee Performance Field Population Registration and Information at the Department of Population and Civil Bekasi. The method used was casual comparative data analysis of multiple regression models with a significance level of 0,05. The result obtained that R2 =0,567 Or 56,7% indicates that work motivation and discipline of 56,7% contribute to the employee performance, while the remaining 43,3% influenced by other independent variables outside the model used.